2011
DOI: 10.3354/meps09394
|View full text |Cite
|
Sign up to set email alerts
|

Restricted dispersal of the reef fish Myripristis berndti at the scale of the SW Indian Ocean

Abstract: The reef fish Myripristis berndti (Jordan & Everman 1903) is a pantropical species. A genetic analysis was conducted on 353 individuals from 10 localities distributed across the SW Indian Ocean (SWIO) in order to determine patterns of connectivity in the SWIO. Both the mtDNA sequences (711-bp cytochrome b sequences) and the microsatellites (8 newly developed loci) reveal spatial patterns of differentiation within the SWIO. There is, however, a discrepancy between the structure observed with each kind of marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 49 publications
10
33
1
Order By: Relevance
“…Both the haplotype networks and pairwise F ST comparisons revealed significant genetic structuring between the NWIO populations (Mayotte and Seychelles islands) and a group made up of the SWIO populations (Madagascar, Réunion, and Mauritius). This pattern is in agreement with what was previously observed in the reef fish Myripristis berndti for which genetic structure analyses indicated an important isolation of Réunion and Madagascar from Mayotte (Muths et al 2011). The geographic isolation and the biogeographic location of Réunion Island (i.e, surrounded by deep-sea areas) and the relative rarity of the species on the neighboring island (i.e., Mauritius) have been proposed to explain the genetic isolation of Réunion populations.…”
Section: The Southwest Indian Ocean (Swio)supporting
confidence: 88%
“…Both the haplotype networks and pairwise F ST comparisons revealed significant genetic structuring between the NWIO populations (Mayotte and Seychelles islands) and a group made up of the SWIO populations (Madagascar, Réunion, and Mauritius). This pattern is in agreement with what was previously observed in the reef fish Myripristis berndti for which genetic structure analyses indicated an important isolation of Réunion and Madagascar from Mayotte (Muths et al 2011). The geographic isolation and the biogeographic location of Réunion Island (i.e, surrounded by deep-sea areas) and the relative rarity of the species on the neighboring island (i.e., Mauritius) have been proposed to explain the genetic isolation of Réunion populations.…”
Section: The Southwest Indian Ocean (Swio)supporting
confidence: 88%
“…Given the reproductive mode of L. brevirostris α, such migrations would be extremely rare events. At smaller geographic scales, within the WIO, previous population genetics studies revealed that oceanic gyres isolate Juan de Nova Island from the Southern part of the Mozambique Channel (Bourjea et al, 2006;Krishna et al, 2006;Muths et al, 2011); our results support these findings. In the Mascarene Islands, the Southeast Madagascar current (Schott et al, 2009) could allow connectivity between Rodrigues and Reunion Island populations, but our results indicate that such gene flow is absent or extremely low.…”
Section: Potential Barriers To Gene Flow and Limited Dispersalsupporting
confidence: 87%
“…Toliara (TOL), in the southern Mozambique Channel, had the most divergent populations (Table , Appendix S2). The result is consistent with a recent genetic study (Muths et al ., ) that highlighted the effect of oceanography on fish connectivity in the region. Our data show that lecithotrophic species have, on average, more limited connectivity than planktotrophic species, confirming previous correlations between dispersal capacity and genetic structure in other marine invertebrates (Goldson et al ., ; Paulay & Meyer, ; Boissin et al ., ).…”
Section: Discussionmentioning
confidence: 99%